Compressive strength of resin-modified glass ionomer restorative material: effect of P/L ratio and storage time (Journal of Applied Oral Science, 2005)
The aim of this study was to evaluate the compressive strength of resin-modified glass ionomer cement Fuji II LC and Vitremer, in powder/liquid ratios of 1:1, 1:2 and 1:3, at three periods (24 hours, 7 and 28 days) of storage in distilled water at 37ºC. For each material, P/L ratio and storage time, 5 cylindrical specimens were prepared, with 4mm diameter and 6mm height, in silicon moulds. Specimens were light-cured for 40 seconds at each extremity, removed from the moulds and laterally light-cured (perpendicular to long axis) for 40 seconds, protected as recommended by the manufacturers and immersed for the time tested. The specimens were submitted to compressive strength testing in an Instron machine at a crosshead speed of 1.0mm/min until failure. Data were submitted to ANOVA and Tukey's test (5%), and showed that the compressive strength of resin-modified glass ionomer cement was reduced when P/L ratio was reduced and that the storage in water had little influence on compressive strength.